LEVANTAMENTO DE NEMATÓIDE DE CISTO DA SOJA Heterodera glycines, NO ESTADO DE SÃO PAULO, BRASIL - Rossi, Carlos Eduardo; Silveira, Salima Gibrin Pinheiro da; Araújo, Ana Cristina Magalhães; Montes, Sonia Maria N.; Guilhem, Dulcinei José; Lopes, Luiz Carlos (REVISTA DE AGRICULTURA, 2015)
LEVANTAMENTO DE NEMATÓIDE DE CISTO DA SOJA Heterodera glycines, NO ESTADO DE SÃO PAULO, BRASIL